2022
DOI: 10.1007/s12144-022-03406-2
|View full text |Cite
|
Sign up to set email alerts
|

Professional and psychological precursors of instructional approaches used in distance learning during COVID-19

Abstract: The current study addresses two antecedents that may serve to explain teachers' online instructional practices during the COVID-19 pandemic: first, the professional aspect that deals with suitable training of teachers and school support for distance learning, and second, informed by the professional aspect, the personal (psychological) aspect that discusses the self-efficacy and attitudes of teachers toward distance learning. A mixed-methods design was employed by collecting data from 327 Israeli schoolteacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The outbreak of the COVID-19 pandemic affected education on a global scale, leading to unprecedented scenarios that required expeditious responses [1,2]. The harsh restrictions and lockdowns imposed in most parts of the world led to massive school closures, forcing educational institutions at all levels to make a sudden and radical transition from faceto-face teaching and learning modes to teaching and learning at a distance [3,4]. This temporary shift in instructional delivery to an online mode due to the pandemic crisis circumstances [5], which came to be known as emergency remote teaching (ERT), posed profound challenges for teachers worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outbreak of the COVID-19 pandemic affected education on a global scale, leading to unprecedented scenarios that required expeditious responses [1,2]. The harsh restrictions and lockdowns imposed in most parts of the world led to massive school closures, forcing educational institutions at all levels to make a sudden and radical transition from faceto-face teaching and learning modes to teaching and learning at a distance [3,4]. This temporary shift in instructional delivery to an online mode due to the pandemic crisis circumstances [5], which came to be known as emergency remote teaching (ERT), posed profound challenges for teachers worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in the early stages of the pandemic indicated that educational systems around the world were not adequately prepared to deal with the rapid changes in teaching methods imposed by ERT [4,[8][9][10]. Teachers, in particular, faced numerous obstacles in adapting to teaching at a distance, both in maintaining a minimum level of communication with students to adequately support and monitor their learning progress and in achieving their instructional goals [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…that ICT-related training programmes improve teachers' computer skills, whether they are novices or seasoned professionals[53]-[55]. To achieve successful innovation integration, school administrators should seek support in order to identify and provide continuous training[56].…”
mentioning
confidence: 99%